Modelling and outdoor performance characterization of monocrystalline and polycrystalline silicon photovoltaic modules - Pamain, Adriano; Rao, P.V. Kanaka (Open Science Journal, 2022)
This paper presents the modeling and outdoor performance of monocrystalline silicon (m-Si) and polycrystalline silicon (p-Si) Photovoltaic (PV) modules. The I – V and P – V characteristics curves obtained by simulation and from outdoor experiments, were used to extract electrical parameters such as open-circuit voltage, short circuit current, maximum current, and maximum voltage. Parameters acquired were further used to compute the maximum power output, fill factor, and conversion efficiency of PV modules. The simulation results obtained were in agreement with the manufacturer’s datasheet value while experimental results showed a slight deviation from Standard Test Condition (STC) values. The effects of solar irradiance, module temperature, quality, and series resistance on the performance of PV modules were considered. It was observed that as solar irradiance increased the performance of PV modules improved, whereas the increase of other parameters such as module temperature, series resistance, and diode ideality factor declined the performance of PV modules. @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073697537 9 0 511 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-GB;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-GB;}div.WordSection1 {page:WordSection1;}